STRATEGIES TO ENHANCE GRADUATE EMPLOYABILITY: INSIGHTS FROM MALAYSIAN PUBLIC UNIVERSITY POLICY-MAKERS - Marfunizah Ma'dan; Muhamad Takiyuddin Ismail; Sity Daud (UUM Press, 2020)
Purpose: This study aims to identify the focus and strategies of Malaysian public universities to enhance graduatesâ€™ competency levels, as well as their key challenges.   Methodology: The study used an exploratory approach, applying a qualitative method. Data were collected at eight selected public universities in Malaysia through face-to-face interviews with expert informants that included a deputy vice chancellor of academic affairs and directors in charge of graduate employability. Content analysis was used to analyse the data.   Findings: The results revealed the practical roles of Malaysian public universities in enhancing graduatesâ€™ competency levels and subsequently securing their employability by meeting market demands. Nonetheless, stronger changes and reforms at the institutional level are needed to support the degree of competency among graduates, such as improving teaching methods and programmes offered. Furthermore, universityâ€"industry collaboration should also be strengthened to develop a competitive and capable talent pool in the country.   Significance: The paper extends the core focus and strategies that have been implemented by public universities by providing more detailed and practical solutions to ensure that curriculum design more effectively supports the development of graduate competency. The study findings are useful for improving universitiesâ€™ strategies and implementation processes to pursue a balanced quality of education in developing future talent.